Hypogean carabid beetles as indicators of global warming? - Pietro Brandmayr; Filippo Giorgi; Achille Casale; Giorgio Colombetta; Laura Mariotti; Augusto Vigna Taglianti; Friedrich Weber; Roberto Pizzolotto (Environmental Research Letters, 2013)
Climate change has been shown to impact the geographical and altitudinal distribution of animals and plants, and to especially affect range-restricted polar and mountaintop species. However, little is known about the impact on the relict lineages of cave animals. Ground beetles (carabids) show a wide variety of evolutionary pathways, from soil-surface (epigean) predatory habits to life in caves and in other subterranean (hypogean) compartments. We reconstructed an unprecedented set of species/time accumulation curves of the largest carabid genera in Europe, selected by their degree of ‘underground’ adaptation, from true epigean predators to eyeless highly specialized hypogean beetles. The data show that in recent periods an unexpectedly large number of new cave species were found lying in well established European hotspots; the first peak of new species, especially in the most evolved underground taxa, occurred in the 1920–30s and a second burst after the 70s. Temperature data show large warming rates in both periods, suggesting that the temperature increase in the past century might have induced cave species to expand their habitats into large well-aired cavities and superficial underground compartments, where they can be easily sampled. An alternative hypothesis, based on increased sampling intensity, is less supported by available datasets.